Business Plan "Cafe with Sugar-Free Desserts" - Zakharova, Alina (2024)
Thesis aims to create a business plan for the bakery “Sweet-Fit” which produces traditional products that everyone likes but without adding sugar. The purpose is to give a detailed description of the business and evaluate the market, implement the business plan in real life, evaluate the risks of opening such as business, and calculate payback for investors. The thesis is divided into two main parts. The theoretical part describes methods and approaches that should be used in the business plan. The practical part of the thesis includes a description of the product and services, different analyses, and research of the market and regulations.